Development of unit hydrograph for estimation of hydrologic response from Chaukhutia watershed - TONDE, JANHAVI; SINHA, B. L.; SINHA, JITENDRA; PALI, A. K. (Journal of Soil and Water Conservation, 2020)
Unit hydrograph is a very important practical tool in runoff prediction, which has been used since many years ago and to date it remains useful. Present study was undertaken to develop an average unit hydrograph for estimating the peak rate of runoff and temporal distribution of direct runoff and simulation of flood hydrograph for Chaukhutia watershed of the Ramganga reservoir catchment. The developed unit hydrograph was calibrated for ten storm events and verified for four storm events. The performance and adequacy tests of the unit hydrograph were also carried out by comparing the computed direct runoff hydrograph with the observed runoff hydrographs. The peak runoff rates as well as direct runoff hydrographs computed by unit hydrograph were in close agreement with the observed direct runoff hydrographs. Various statistical measures were used for testing its reliability. A mathematical relationship between observed and computed peak runoff rates with effective rainfall, was also established on storm basis and it was found in very close relationship with each other